HOW MOBILE PHONE SURVEILLANCE CONTRIBUTES TO DIGITAL INEQUALITIES FOR DISADVANTAGED URBAN RESIDENTS - Fernback, Jan; Shaffer, Gwen (AoIR Selected Papers of Internet Research, 2015)
Participation in the social world demands disclosure of personal information, and the increasing reliance on mobile devices compounds this reality. Americans routinely communicate through mobile apps such as Facebook, Instragram and Skype. Consumers skip the mall and, instead, make purchases on their smart phones. And more than one-third of all Internet searches originate on a mobile phone (Statista, 2013). Within each of these contexts, Americans willingly disclose—or inadvertently reveal—their political opinions, values and personal interests. And Americans living in disadvantaged urban communities often rely exclusively on mobile devices for accessing the Internet. This study explores the potential for the “digital imaginary” to obscure inequalities. It examines: in what way is social capital for the urban poor impacted by the tracking, storing and possible disclosure of their information? Because private information obtained through mobile surveillance is often used in discriminatory ways, what implications exist for managing digital inequalities?